High Glycemic Diet Is Related to Brain Amyloid Accumulation Over One Year in Preclinical Alzheimer's Disease - Taylor, Matthew K.; Sullivan, Debra K.; Morris, Jill K.; Vidoni, Eric D.; Honea, Robyn A.; Mahnken, Jonathan D.; Burns, Jeffrey M. (Frontiers in Nutrition, 2021)
Objective: To test the hypothesis that high glycemic diet is related to 1-year change in brain amyloid based on our prior cross-sectional evidence that high glycemic diet is associated with brain amyloid. Methods: This longitudinal, observational study assessed the relationship between reported habitual consumption of a high glycemic diet (HGDiet) pattern and 1-year brain amyloid change measured by Florbetapir F18 PET scans in 102 cognitively normal older adults with elevated or sub-threshold amyloid status that participated in a 1-year randomized, controlled exercise trial at the University of Kansas Medical Center in Kansas City. Results: Among all participants (n = 102), higher daily intake of the HGDiet pattern (β = 0.06, p = 0.04), sugar (β = 0.07, p = 0.01), and total carbohydrate (β = 0.06, p = 0.04) were related to more precuneal amyloid accumulation. These relationships in the precuneus were accentuated in participants with elevated amyloid at enrollment (n = 70) where higher intake of the HGDiet pattern, sugar, and carbohydrate were related to more precuneal amyloid accumulation (β = 0.11, p = 0.01 for all measures). In individuals with elevated amyloid, higher intake of the HGDiet pattern was also related to more amyloid accumulation in the lateral temporal lobe (β = 0.09, p < 0.05) and posterior cingulate gyrus (β = 0.09, p < 0.05) and higher sugar and carbohydrate intake were also related to more amyloid accumulation in the posterior cingulate gyrus (β = 0.10, p < 0.05 for both measures). Conclusion: This longitudinal observational analysis suggests that a high glycemic diet relates to higher brain amyloid accumulation over 1 year in regions of the temporoparietal cortex in cognitively normal adults, particularly in those with elevated amyloid status. Further studies are required to assess whether there is causal link between a high glycemic diet and brain amyloid. Clinical Trial Registration:ClinicalTrials.gov, Identifier (NCT02000583).